Fiber Orientation In Short Fiber Reinforced Thermoplastic Composites - Ahmad Johari, Ahmad Abdullah (Universiti Teknologi Petronas, 2004)
The objective of this project basically is to study the fiber orientation in short fiber reinforced thermoplastic composites especially at the geometry where the convergence and divergence flow is expected to occur. The material used for the study is chopped glass fiber 3mm in length as the reinforcement and high density polyethylene as the matrix. The study also includes a comparison of fiber orientation and the mechanical properties of the composites with different volume fraction of glass fiber. The volume fraction used is 5%, I 0%, 15% and 20% of glass fiber. The mold for the sample is using the standard shape for tensile test or called "dumbbell" shape. The advantage of this mold is able to investigate both the fiber orientation and the mechanical properties using the same mold geometry. The samples are produced using injection molding process with controlled parameters. The samples are characterized using micrographic test for the fiber orientation study and tensile test for the mechanical properties determination. The results show the fiber orientation in the sample confirm with the expected result with slight variation due to processing effects. While for the mechanical test show as the volume fraction increase the Young Modulus also increase. Therefore can be concluded that volume fraction of glass fiber have an effects to the fiber orientation and mechanical properties of the composite.